PEMANFAATAN CITRA SATELIT DALAM KAJIAN KESESUAIAN KONVERSI LAHAN PERTANIAN KE NON PERTANIAN TERHADAP RENCANA TATA RUANG KABUPATEN SEMARANG - M Luthfi Syifaul Karim; Sri Rahayu (Geoplanning: Journal of Geomatics and Planning, 2014)
The increase of population, facilities, infrastructure, and settlement area are among the indicators of urban development. It is characterized by, among others, land use conversion as happens in East-Ungaran District (Kecamatan) of Semarang Regency (Kabupaten). Problems arise when the conversion is not in compliance with the spatial plan, for example the change of agricultural land to non-agricultural one in the most of Kecamatan East-Ungaran. This research is conducted using spatial analysis tools such as remote sensing and image processing techniques to analyze the area of agricultural land that has been converted to non-agricultural one. Results of the image interpretation using GIS and satellite imagery processing show that from 2008 to 2011 the total conversion is 30.40 Ha, most of which is for roads and settlement area. Therefore, a strict regulation is needed to control the land conversion. In this case, further study is recommended to formulate effective regulation and measures in controlling the problematical land conversion.